Larvicidal effects of some plant seed extracts on Anopheles annularis Vander Wulp and Culex quinquefasciatus Say (Diptera: Culicidae) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
Larvicidal effects of distilled water, 50% ethyl alcohol, acetone and methanol extracts on seed of four plants viz. Sinapis alba (Linn.), Carica papaya (Linn.), Momordica charantia (Linn.) and Capsicum annuum (Linn.) were studied upon the mosquito larvae of Anopheles annularis Vander Wulp and Culex quinquefasciatus Say under normal laboratory conditions with average temperature and relative humidity of 31.1oC and 57.6%, respectively. Percentage mortality, probit mortality, chi-square and ANOVA values for the larvae, extracts and concentrations were calculated for 24 hours exposure period. Mortality was dose dependent. The values of LC50 of the seeds of S. alba on An. annularis at the application doses for the distilled water, 50% ethyl alcohol, acetone and methanol extracts were 3431.791, 1038.363, 1254.810 and 2269.975 ppm, respectively; for C. papaya were 804.008, 403.294, 597.165 and 573.241 ppm, respectively; for M. charantia were 10593.241, 5017.710, 5650.191 and 6075.204 ppm, respectively; and for C. annuum were 1274.968, 4637.201, 1604.852 and 1905.692 ppm, respectively. The values of LC50 of S. alba seeds on Cx. quinquefasciatus at the application doses for the distilled water, 50% ethyl alcohol, acetone and methanol extracts were 1415.311, 432.996, 569.701 and 770.250 ppm, respectively; for C. papaya were 705.599, 385.688, 341.003 and 481.067 ppm, respectively; for M. charantia were 7764.154, 4496.464, 5353.759 and 5825.031 ppm, respectively; and for C. annuum were 2173.631, 1311.538, 78.748 and 182.869 ppm, respectively. Of the four plant seed extracts, C. papaya seed extracts were the most toxic for both the mosquito species.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 41-52